Transforming modern representative democracy via advanced telecommunications: voting from the home, deliberative polling, electronic town meetings, the Internet - Becker, Theodore; Slaton, Christa Daryl (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 1997)
We live in a time of great, unique and extremely rapid change. In terms of human communications, we are experiencing a time of profound transformation. And though many predicted this epoch, even envisioned it, it still comes as a surprise. Because as is the case in any transformational era, one gets carried along with the completely unpredictable surge of events and how novel technologies are being used in totally new ways and with wholly unintended consequences.